Relationships between the environment and structure of the fish community in nycthemeral cycles in the Mecoacán lagoon, Tabasco, Mexico - Ayala-Pérez, Luis Amado; Castillo-Adame, Iliana Lizeth; Esquivel- Herrera, Alfonso; Estrada-Hidalgo, Nayelli; Jardon-Romero, Jennifer Pamela; Jiménez-Obregón, Itzel; Rodríguez-Ayala, Eduardo André (Revista Ciencias Marinas y Costeras, 2022)
The Mecoacán lagoon is an ecosystem used as a breeding area, a refuge, and a feeding and growth area by different species, particularly mollusks, crustaceans, and fish. The objective of this study is to compare the relationships between the environment and the structure of the fish community between two nycthemeral cycles, at a site near the mouth connecting a lagoon with the sea. Two sampling campaigns were carried out during June and October 2019, recording environmental variables and collecting samples of ichthyofauna with a gillnet. Abundance was determined in terms of number of individuals, biomass, and average weight, as well as heterogeneity, species diversity, and evenness indices. Dominant species were identified, ecological associations were analyzed and the correlations between abundance and environmental variables were determined. The average temperature was 29.6 °C, average salinity was 30.46 units, average dissolved oxygen was 2.28 mg/l and average pH was 7.46. In total, 16 species of fish were identified, among which the abundance of Diapterusrhombeus stands out. In June 13 species belonging to 12 genera and 11 families were reported, while in October 10 species were captured, belonging to 9 genera and 8 families. Eleven (11) dominant species were identified that can be classified into four groups which show differential correlations with environmental variables. Given the various anthropogenic pressures operating in the lagoon, it is important to integrate information on the environment and the structure of biotic communities as a basis for evaluating their degree of disturbance.